Collaborative Research Networks in Educational Institutions: A Sociological Analysis of Knowledge Sharing Patterns among Academic Communities - Sumual, Tinneke Evie Meggy; Montolalu, Steven; Roring, Venny Y; Tulangow, Yersi F; Karundeng, Ferry; Samalo, Dodi Christofel; Tuerah, Paulus Robert (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
This study explores the dynamics of collaborative research networks in Indonesian educational institutions through a sociology of knowledge approach. The main objective of the study is to analyze the pattern of knowledge sharing and the transformation of the academic ecosystem in the context of globalization. An interpretive qualitative method is used, including literature studies, in-depth interviews, and theoretical analysis based on grounded theory with a sample of cross-disciplinary researchers. The research findings reveal three key aspects: (1) the structure of the research network that is dynamic and heterarchical, (2) the mechanism of knowledge sharing that is multimodal and influenced by social capital, and (3) the transformation of the research ecosystem towards a transdisciplinary model. The study recommends the development of policies that support collaboration flexibility, investment in social capital, and strengthening digital infrastructure to support innovative and responsive research networks.